International Workshop on Dynamic Behaviour of Structures and Materials, Interaction and Friction Across the Strain Rates - 2015, PETER (Engineering Transactions, 2015)
The workshop will cover both theoretical modelling of the mechanical behavior of materials and structures under dynamic loading and all aspects related to friction and contact.There will be eight main themes:1. Constitutive relations and modelling2. Numerical simulations3. Perforation and Impact4. Crashworthiness5. Experiments and inverse methods6. Friction and interaction7. Surface and contact8. Shock and Blast Loading